2017
DOI: 10.1161/strokeaha.116.016293
|View full text |Cite
|
Sign up to set email alerts
|

MIDAS (Modafinil in Debilitating Fatigue After Stroke)

Abstract: Background and Purpose—This study aimed to assess the efficacy of modafinil, a wakefulness-promoting agent in alleviating post-stroke fatigue ≥3 months after stroke. We hypothesized that 200 mg of modafinil daily for 6 weeks would result in reduced symptoms of fatigue compared with placebo.Methods—This single-center phase 2 trial used a randomized, double-blind, placebo-controlled, crossover design. The key inclusion criterion was a multidimensional fatigue inventory score of ≥60. Patients were randomized to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 25 publications
0
50
0
2
Order By: Relevance
“…Most of the interventional studies have a medium to high risk of bias. Table 2 shows only two studies in white cells (indicating low risk of bias) but both have small sample size consisting of 34 (MIDAS study 63 68 ) and 64 randomised patients 61 respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the interventional studies have a medium to high risk of bias. Table 2 shows only two studies in white cells (indicating low risk of bias) but both have small sample size consisting of 34 (MIDAS study 63 68 ) and 64 randomised patients 61 respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The dominance of single-centred interventional studies with small sample sizes and interventions delivered within a 12-week period may be the reasons for absence of follow-up studies. MIDAS (interventional) 63 65 and NotFAST (observational) 81 85 are the only recent studies with novel and potentially long-term findings with larger sample size (in case of MIDAS 2) 103 or with the intention to design an intervention (NotFAST2) 104 .…”
Section: Discussionmentioning
confidence: 99%
“…Beta coefficients with their 95% confidence intervals and Pearson’s correlation coefficients were estimated. Differences in pre- and post-treatment quality of life were compared to differences in pre- and post-treatment fatigue, which had been demonstrated to be improved by modafinil ( 2 ). Treatment effects and interactions between treatment and baseline measures were assessed using linear regression including fixed effects for participant, treatment (modafinil or placebo), baseline outcome measure, and interaction between treatment and baseline measure.…”
Section: Methodsmentioning
confidence: 99%
“…Approximately 40% of stroke survivors experience debilitating fatigue 3 months or more after their stroke which can negatively impact their quality of life, interfering with their ability to participate in rehabilitation and return to everyday activities such as work and socialization ( 1 ). We recently investigated the effectiveness of the wakefulness-promoting agent modafinil in stroke survivors as part of the modafinil in debilitating fatigue after stroke (MIDAS) trial ( 2 ). During MIDAS, participants reported a significant decrease in fatigue following 6 weeks of modafinil therapy (200 mg/day) and a concurrent improvement in self-reported quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated a surprising correlation between modafinil and neuroprotection (Han, Chen, Liu, & Zhu, 2018). This compound decreases the fatigue in stroke survivors (Bivard et al, 2017). It was reported that the intraperitoneal (i.p.)…”
Section: Introductionmentioning
confidence: 99%